Current Issues, Opportunities, and Horizons in Literacy Studies in Latin America - Moreno-Mosquera, Emilce; Soares Sito, Luanda Rejane (Íkala, Revista de Lenguaje y Cultura, 2019)
To open this issue, we as guest editors aim to reflect on some fundamentals supporting literacy studies, and how these could be relevant to education in Latin America. New Literacy Studies (also called New Written-Culture Studies) account for a shift in how we understand literacy practices approach and acquisition in given cultural contexts, versus mainstream cognitive models, in a rather experimental and individualistic approach. To accomplish this aim, we will explain how our interest on this topic aroused, and which role language, and reading and writing practices play in literacy studies, to end up suggesting lines of action open and relevant to education in Latin America.